Cytokines in stools of children with inflammatory bowel disease or infective diarrhoea. Issue 8 (August 1993) - Nicholls, S; Stephens, S; Braegger, C P; Walker-Smith, J A; MacDonald, T T
Abstract : AIMS–To determine the concentrations of interleukin-6 (IL-6) and tumour necrosis factor alpha (TNF alpha) in stools from children. METHODS–Stool samples from 14 healthy children, 32 children with inflammatory bowel disease, and 23 children with acute diarrhoea were emulsified in an equal volume of phosphate buffered saline and then centrifuged to produce a clear supernatant fluid. IL-6 and TNF alpha were measured by enzyme linked immunosorbent assay (ELISA). RESULTS–TNF alpha was detected in the stools of all 14 healthy children (12-130 pg/g stool), but IL-6 was detected only in three. Similar results were seen in children with inactive inflammatory bowel disease. Stool TNF alpha concentrations were raised in samples from children with active inflammatory bowel disease, but in most (11/18) of these samples IL-6 was undetectable. Stool samples contained a heat-labile factor which rapidly destroyed IL-6 immunoreactivity. Most children with diarrhoea had TNF alpha concentrations similar to those of healthy controls and most were also negative for IL-6. Three children with Shigella flexneri infection had extraordinarily high concentrations of both TNF alpha and IL-6 in their stools. CONCLUSIONS–There is constant low grade production of TNF alpha in the intestine of healthy people. Raised values are indicative of mucosal inflammation, but are not specific. Stool IL-6 is of little use in assessing mucosal inflammation because immunoreactivity is rapidly lost in stool samples.